HOW DOES THE WORK SHIFT AFFECT THE EMOTIONAL STATE AND INTERPERSONAL RELATIONSHIPS OF POLICE OFFICERS? - Shahrizad Rafil Imanova (International Journal of Innovative Technologies in Social Science, 2025)
Law enforcement is a demanding profession, characterized by high levels of occupational stress, unpredictable environments, and non-standard work schedules. Among the various occupational stressors, irregular and extended work schedules have emerged as significant contributors to police officers’ emotional strain and deteriorating interpersonal relationships. This study explores how work schedules affect the psychological well-being and personal lives of police officers, drawing from studies in occupational health, psychology, and criminal justice. Methods: The quantitative research methods as survey, and measurement scale were used based on constructive approach. 100 police members participated in the study during 2024-2025 years. The positive statistical correlation was mentioned between work shift and emotional issues of the police members (officers, and sergeants). More longer work hours were observed more emotional problems, and burnout syndrome in their mental and physical states. These findings highlight the need for law enforcement agencies to consider the human cost of scheduling practices and to implement systemic changes that promote both officer well-being and public safety.